Incidence de la politique scientifique fédérale sur l’économie québécoise - Julien, Pierre-André (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
In the first part of this paper, the federal expenditures affecting the scientific activity of the province of Quebec, directly or indirectly, are identified. In the second part, there is an attempt to measuring the impact on the economy of those expenditures. Finally, a comparison is made with the situation that prevails in the other provinces, on that matter.